Whistleblowing bounties and informational effects - Nan, Lin; Tang, Chao; Zhang, Gaoqing (Journal of Accounting and Economics, 2024)
We examine the impact of increasing whistleblowing bounties on whistleblowers' strategy and regulatory efficiency in detecting fraud. Our analysis shows the regulator extracts information about the incidence of fraud from whistleblowers' actions, and the quality of such information depends on the size of whistleblowing bounties. With a larger bounty, upon receiving a whistleblowing report, the quality of the regulator's information about fraud deteriorates, whereas upon observing no whistleblowing, the information quality about no fraud improves. Although the informational improvement upon no whistleblowing has not been widely discussed, we demonstrate it is a key determinant of the optimal whistleblowing program. We show, considering the informational value of whistleblowing and no whistleblowing, the regulator should set the bounty to encourage more whistleblowing when the prior belief of fraud is stronger and the insider is better informed. Our analysis generates policy and empirical implications for designing and studying whistleblowing programs.